EXPRESSION PROFILE OF SEX DETERMINATION GENE, BIOREPRODUCTION, PHENOTYPE, AND LOCOMOTORY PERFORMANCES OF OLIVE RIDLEY, Lepidochelys olivacea INDUCED BY DIFFERENT INCUBATION TEMPERATURE - Alfred O. M. Dima; Dedy D. Solihin; Wasmen Manalu; Arief Boediono (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2015)
Sex determination in turtle species is not only based on genotype, but also rely on the incubation temperature. In addition, sexual differentiation takes place during the thermo-sensitive period (TSP). This study was conducted to determine the effects of incubation temperature on sex expression profile of determination gene, bioreproduction, phenotype, and locomotory performances  of olive ridley turtle hatchlings. Fertile eggs incubated at two temperatures, namely feminine temperature (30-33°C), and masculine temperature (26-27°C). Value of cycle threshold (CT) measured during TSP, i.e 23-25 embryonic development stage, and after TSP, i.e 26-27 embryonic development stage using real time PCR techniques. Comparison of gene expression at both incubation temperatures were analyzed by ANOVA, and Student’s t test. Hatchling bioreproduction and phenotype measurement consist of the incubation period, embryo growth, morphometrics, and locomotori performances hatchlings were analyzed with regression analysis and Student’s t test. The results showed expression of both aromatase and Rspond 1 genes (which plays a role in ovarian differentiation) after the TSP that incubated at feminine temperature higher and different with masculine temperature. In conjunction with the  bioreproduction and phenotype, the incubation period of feminine temperature shorter than that of masculine. Likewise, growth of the embryo of feminine temperature was faster than that of masculine. Incubation at feminine temperature significantly affect to carapace width, length and width of the plastron, long flippers and rear arms, long neck, and the frequency of the swing flippers. Keywords: thermo-sensitive period (TSP), gene expression, phenotype, Lepidochelys olivacea